KEPASTIAN HUKUM PENERAPAN INDIRECT EVIDENCE DALAM PENANGANAN KASUS KARTEL DI INDONESIA - Muhammad Akbar; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2021)
Business competition regulations are regulated in law number 5 of 1999. Cartel is one of the prohibited agreements contained in article 11 of law number 5 of 1999. To prove violations of business competition in cartel cases, the Business Competition Supervisory Commission ( KPPU) requires indirect evidence to prove the existence of a cartel agreement between business actors. There are two types of indirect evidence, including communication evidence and economic evidence. Proof using indirect evidence in law enforcement of law number 5 of 1999 is very necessary given that it is very difficult to prove cartel practices. This is because business actors do it secretly and secretly. However, the existence of indirect evidence is still being debated and is considered to have no legal certainty because indirect evidence is not explicitly stated in Law number 5 of 1999 but the existence of indirect evidence is widely recognized in the enforcement of competition law in various countries.